THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT: AN APPLIED STUDY ON MUSTANSIRIYAH UNIVERSITY IN IRAQ - Omar Ahmed Jasim (Scholars Digest Publishing, 2025)
The research aims to examine the relationship between organizational culture and organizational commitment at Al-Mustansiriyah University in Iraq, The research adopted a descriptive–correlational approach and was conducted on a sample of 165 employees during the year 2021, Two questionnaires were employed to measure organizational culture and organizational commitment, with reliability coefficients of 0.89 and 0.88 respectively, as assessed by Cronbach’s Alpha. Data were analyzed statistically using SPSS version 26 at a significance level of (P < 0.05). The findings revealed a positive and statistically significant relationship between organizational culture and organizational commitment (r = 0.419, P = 0.027), Furthermore, a moderate positive relationship was identified between organizational culture and each of affective commitment, continuance commitment, and normative commitment. The study concluded that fostering a positive organizational culture enhances employees’ loyalty and sense of belonging, which in turn contributes to improving organizational performance and job satisfaction. The research recommended adopting managerial policies that emphasize positive organizational values such as justice, efficiency, and teamwork, alongside providing both material and moral support to employees in order to strengthen their organizational commitment and ensure stability and sustainability within the university environment.
Keywords: Organizational Culture, Organizational Commitment, Affective Commitment, Continuance Commitment, Normative Commitment.